Otopsi Linguistik Forensik Pada Tuturan Perundungan Siber di Media Sosial Tiktok: Studi Kasus Pemilihan Umum Tahun 2024 - Sandi, Rizki Junando; Sawirman, Sawirman; Aslinda, Aslinda (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2024)
Freedom of speech on social media often gives rise to acts of cyber-bullying aimed at insulting, offensive, and degrading individuals or groups. The use of language as a tool to perpetrate cyber-bullying deserves further attention. This research aims to analyze forensic linguistic autopsy of cyber-bullying speech on social media Tiktok with a case study of the 2024 General Election. This research is qualitative research with stages of data collection and analysis carried out through observation, textual techniques and lingual data recording, so that followed by comparing the data referentially. The results of research on cyberbullying speech on social media Tiktok with a case study of the 2024 General Election, specifications for the Presidential and Vice Presidential Election for the period 2024-2029 found 15 evidence of language having a legal impact, namely palak ayahkau, Anies cukimai, stupid, melehoy, Mbah Wowo & Samsul, belegug, otak kosong, bacot, Ganjar bokep, Rohingya President, selling satay, tuelek, tuek, and cocot are connected in every profile. Based on the results for this research prove that cyber-bullying is often used by Tiktok social media users to attack and insult presidential and vice presidential candidates in the 2024 elections.